Reshaping a retained deciduous canine with a semidirect composite resin veneer: A clinical report - Benitez Sellan, Pablo Lenin [UNESP]; Bresciani, Eduardo [UNESP] (Elsevier, 2019)
The presence of a retained primary canine in an adult, although not frequent, affects esthetics. Choosing the optimal restorative treatment is a challenge. The present clinical report describes a treatment for tooth reshaping with a semidirect composite resin technique, achieving an excellent esthetic result. The treatment was successful at the 18-month follow-up.